Developments in the Coordination Chemistry of Phosphinines1. Issue 2 (7th November 2012) - Müller, Christian; Broeckx, Leen E. E.; de Krom, Iris; Weemers, Jarno J. M.
Abstract: This microreview describes progress in the development and coordination chemistry of donor‐functionalized phosphinines – the phosphorus analogues of pyridines – that has been made during the last five years. The stepwise assembly of 2, 4, 6‐triarylphosphinines starting from functionalized benzaldehyde and acetophenone derivatives allows the incorporation of additional substituents into specific positions of the aromatic phosphorus heterocycle. This strategy can be used to synthesize chelating phosphinines, which is an essential aspect especially for the preparation of phosphinine‐based transition metal complexes containing metal centres in medium‐to‐high oxidation states. Access to such coordination compounds used to be very difficult because monodentate phosphinines cannot be used for this purpose, due to their weak σ‐donor properties but strong π‐accepting capacities. Moreover, metal complexes of less highly substituted phosphinines turned out to be extremely sensitive to nucleophilic attack, making their straightforward synthesis, characterization and application rather unattractive. The recent strategies in this area facilitate synthetic access to a completely new set of phosphinine‐metal complexes for the first time, leading to a much broader scope for potential applications. New developments in the areas of homogeneous catalysis and materials sciences can consequently be foreseen in the near future. Abstract : We highlight recent achievements in the design of donor‐functionalized, chelating 2, 4, 6‐triarylphosphinine derivatives by the pyrylium salt route and illustrate strategies to access new neutral and cationic phosphinine‐based transition metal complexes containing metal centres in various oxidation states, such as M 0, M I, M II and M III . Comparisons with isostructural nitrogen analogues are made.